1997
DOI: 10.1182/blood.v89.6.2210
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Human B-Chronic Lymphocytic Leukemia in Human/Mouse Radiation Chimera: Evidence for Tumor-Mediated Suppression of Antibody Production in Low-Stage Disease

Abstract: B-chronic lymphocytic leukemia (BCLL) is a lymphoproliferative disease that is characterized by clonal expansion of CD5+ B cells. BCLL is associated with secondary immunodeficiency and hypogammaglobulinemia. It has been suggested that T-cell dysregulation may play a role in the hypogammaglobulinemia and in the increased incidence of autoimmunity in BCLL patients. We attempted to transfer human peripheral blood mononuclear cells (PBMC) from BCLL patients in different stages of the disease into immunodeficient m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Soon after the discovery of scid mice, it was shown that lethally irradiated normal (immunocompetent) mice transplanted with C.B-17-scid marrow, followed later by a large dose of human bone marrow, resulted in low levels of human cell engraftment [41]. This model has been used to study human stem cell phenotype and differentiation [41], as well as the growth of human leukemias and lymphomas in vivo [64]. However, in these irradiated, scid marrow-engrafted, human marrow-injected mice, the role of natural antibodies derived from the irradiated immunocompetent host remains a potential obstacle [65].…”
Section: Triple-chimeric (Trimera) Micementioning
confidence: 99%
“…Soon after the discovery of scid mice, it was shown that lethally irradiated normal (immunocompetent) mice transplanted with C.B-17-scid marrow, followed later by a large dose of human bone marrow, resulted in low levels of human cell engraftment [41]. This model has been used to study human stem cell phenotype and differentiation [41], as well as the growth of human leukemias and lymphomas in vivo [64]. However, in these irradiated, scid marrow-engrafted, human marrow-injected mice, the role of natural antibodies derived from the irradiated immunocompetent host remains a potential obstacle [65].…”
Section: Triple-chimeric (Trimera) Micementioning
confidence: 99%
“…Most CLL xenograft mouse models so far use conditioning regimens like irradiation or chemotherapy to prime the mice before CLL injection, with the consequence of destroying or at least changing the hematopoietic stem cell niche and the microenvironment in primary and secondary lymphoid organs [24,31]. Furthermore allograft settings were introduced to improve the CLL engraftment by adding allogeneic CD34+ cord blood cells and antigen presenting allogeneic CD14+ monocytes or CD19+ B cells, with the consequence of unforeseeable immunological changes in CLL biology [27].…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent such implications on the microenvironment and the immune system, we intended to develop a CLL xenograft protocol without any conditioning regimens. Furthermore, we aimed to focus on early stage, and good prognosis CLL samples, as they are underrepresented in the previous studies despite their frequent occurrence [24,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few years, NOD/LtSz-prkdc scid /prkdc scid (non-obese diabetic-severe combine immunodeficiency; NOD-scid) mice grafted with human peripheral blood lymphoid cells (PBLs) have been used as in vivo models for studying transplantation of haematolymphoid cells, human tumour biology, and humanspecific infection agents such as human immunodeficiency virus (HIV). [1][2][3][4] This mouse strain supports levels of human cell grafting that are five-to 10-fold greater than those obtained in C.B-17-scid mice. 5 As a result, the human PBL-NOD-scid model is employed for long-term in vivo analysis of immunoregulatory interactions between human lymphocyte activation and pathogens such as HIV.…”
Section: Introductionmentioning
confidence: 99%